Direct production of polyhydroxybutyrate from waste starch by newly-isolated Bacillus aryabhattai T34-N4. Issue 25 (9th November 2020) - Bomrungnok, Wichittra; Arai, Takamitsu; Yoshihashi, Tadashi; Sudesh, Kumar; Hatta, Tamao; Kosugi, Akihiko
ABSTRACT: Polyhydroxybutyrate (PHB) is a natural microbial polyester produced by a variety of bacteria and archaea from renewable resources. PHB resembles some petrochemical plastics but is completely biodegradable. It is desirable to identify suitable microbial strains and develop processes that can directly use starch from agricultural wastes without commercial amylase treatment. Here, PHB production using starch from agricultural waste was developed using a newly isolated strain, Bacillus aryabhattai T34-N4. This strain hydrolyzed cassava pulp and oil palm trunk starch and accumulated up to 17 wt% PHB of the cell dry weight. The α-amylase of this strain, AmyA, showed high activity in the presence of cassava pulp starch (69.72 U) and oil palm trunk starch (70.53 U). High expression of amyA was recorded in the presence of cassava pulp starch, whereas low expression was detected in the presence of glucose. These data suggest that starch saccharification by amyA allows strain T34-N4 to grow and directly produce PHB from waste starch materials such as cassava pulp and oil palm trunk starch, which may be used as low-cost substrates. GRAPHICAL ABSTRACT: UF0001